Environmental policy and management in the context of security and economic development in Malaysia - Mariyappan, Raman (Universitas Islam Riau Indonesia, 2010)
This paper looks at the policy implications on environmental issues in Malaysia in order to enjoy its security and development without jeopardizing its natural environment. In doing so, this paper is divided into four topics. First, the meaning of environment in security and development is deliberated to determine the changes due to economic development. Secondly, the environmental policies and management in maintaining security and in promoting development without damaging the environment. Thirdly, appropriate incorporation of national, regional and global natural resources to support such policies are recommended for due consideration by policy makers. Fourthly, the future challenges and problems are considered in environmental policies and management in Malaysia. Studies have shown that developed countries with exception of United States and a number of European countries (Thomas Sterner, 1999), had scarified their environment in order to achieve the present economic success. Malaysia has achieved significant economic growth during the last two decades, which secures security and further development. Security and economic development can be jeopardized, if implementation of environmental policy and management is not properly addressed. Malaysia experienced a unique situation, where a significant economic development has been achieved without sacrificing most natural environment. But, the recent shift towards tourism, eco-tourism, education, heavy industrial such as automobile and oil refinery has created new environmental problems. If above development trends continues, the present balance between economic development and natural environmental sustainability cannot be maintained in the longer term. The government’s prime concern is to formulate appropriate macroeconomic policies for the prevention, protection and preservation of existing environmental qualities in the country. Increasingly concerned being expressed about the serious threats to the environment, natural resource base, and human health posed by rapid economic growth. The Government needs to respond to these environmental threats with effective policies that strive to integrate economic and environmental policy making. However, political scenario paints a different picture, balance economic and environmental considerations and to turn environmental programs into concrete action is emerging only slowly